Oracle Solaris and Veritas cluster : an easy-build guide - Upreti, Vijay Shankar (Expert's voice in computer science., 2016)
This book shows you how to implement a cluster on your desktop or laptop devices using virtualized network, host, and storage configuration. It explains both the architecture design and technical implementation for building Solaris Oracle- or Veritas-based clustered environments; provides snapshot-based steps to set up Solaris virtual hosts under VirtualBox and implement Veritas clustering across two virtual hosts that can be implemented on a desktop or laptop; will help you understand what it's like setting up a clustered environment, in simple steps that can be followed by users having little knowledge of clustering; implement both Oracle/Solaris and Veritas clusters under Oracle Solaris 10 OS; master cluster fundamentals, concepts, and design; create virtualized environments under VirtualBox; learn the prerequisites and configuration for host builds, networking, and storage setup using VirtualBox for Solaris Oracle and Veritas. --